Magnetic resonance angiography reveals increased arterial blood supply and tumorigenesis following high fat feeding in a mouse model of triple‐negative breast cancer. (5th August 2020) - Mustafi, Devkumar; Valek, Rebecca; Fitch, Michael; Werner, Victoria; Fan, Xiaobing; Markiewicz, Erica; Fernandez, Sully; Zamora, Marta; Mueller, Jeffrey; Olopade, Olufunmilayo I.; Conzen, Suzanne D.; Brady, Matthew J.; et al.
Abstract : Breast cancer is the second most commonly diagnosed malignancy among women globally. Past MRI studies have linked a high animal fat diet (HAFD) to increased mammary cancer risk in the SV40Tag mouse model of triple‐negative breast cancer. Here, serial MRI examines tumor progression and measures the arterial blood volume feeding mammary glands in low fat diet (LFD) or HAFD fed mice. Virgin female C3(1)SV40Tag mice ( n = 8), weaned at 3 weeks old, were assigned to an LFD ( n = 4, 3.7 kcal/g, 17.2% kcal from vegetable oil) or an HAFD ( n = 4, 5.3 kcal/g, 60% kcal from lard) group. From ages 8 to 12 weeks, weekly fast spin echo MR images and time‐of‐flight (TOF) MR angiography of inguinal mammary glands were acquired at 9.4 T. Following in vivo MRI, mice were sacrificed. Inguinal mammary glands were excised and fixed for ex vivo MRI and histology. Tumor, blood, and mammary gland volumes for each time point were measured from manually traced regions of interest; tumors were classified as invasive by histopathology‐blinded observers. Our analysis confirmed a strong correlation between total tumor volume and blood volume in the mammary gland. Tumor growth rates from weeks 8‐12 were twice as high in HAFD‐fed mice (0.42 ± 0.14/week) as in LFD‐fed mice (0.21 ± 0.03/week), p < 0.004. Mammary gland blood volume growth rate was 2.2 times higher in HAFD mice (0.29 ± 0.11/week) compared with LFD mice (0.13 ± 0.06/week), p < 0.02. The mammary gland growth rate of HAFD‐fed mice (0.071 ± 0.011/week) was 2.7 times larger than that of LFD‐fed mice (0.026 ± 0.009/week), p < 0.01. This is the first non‐invasive, in vivo MRI study to demonstrate a strong correlation between an HAFD and increased cancer burden and blood volume in mammary cancer without using contrast agents, strengthening the evidence supporting the adverse effects of an HAFD on mammary cancer. These results support the potential future use of TOF angiography to evaluate vasculature of suspicious lesions. Abstract : This manuscript reports that high animal fat diets (HAFDs) produce higher tumor incidence, tumor burden and tumor aggressiveness in a mouse model of human triple‐negative breast cancer. Mammary gland blood volume and vascular densities increased, showing the first direct correlation between tumor burden and arterial blood volume. This study provides insight into the HAFD effects on breast cancer incidence and aggressiveness and into the changes in the blood volume/vessels associated with in situ cancers and progression to invasive stages.